Tinjauan Pustaka: Graves’ Ophthalmopathy Sebagai Manifestasi Penyakit Graves - Khairani, Ayudia Citra; Wardhani, Gustri Kusuma; Mokoginta, Saskia Nassa (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Graves’ ophthalmopathy (GO), also known as thyroid eye disease, is the most common extrathyroidal autoimmune manifestation of Graves’ disease, significantly affecting visual function and patients’ quality of life. It is characterized by progressive inflammation of the extraocular muscles, orbital fat, and connective tissue, leading to proptosis, diplopia, and optic neuropathy. The pathogenesis of GO involves complex interactions among genetic, immunologic, and environmental factors, with antibodies against the thyroid-stimulating hormone receptor (TSHR-Ab) and insulin-like growth factor-1 receptor (IGF-1R) as major triggers. Diagnosis is based on clinical evaluation, thyroid function testing, and imaging such as MRI or CT scans. Management includes thyroid function control, systemic glucocorticoids, immunosuppressive therapy, radiotherapy, and orbital decompression surgery in severe cases. The prognosis varies depending on early detection, disease severity, and treatment response. Preventive strategies include smoking cessation, maintaining euthyroid status, and early detection using inflammatory biomarkers and advanced imaging technologies.